Studies on freshwater Entomostraca in Greenland IV. - Røen, Ulrik (Meddelelser om Grønland, 1970)
A collection of 14 samples from 10 freshwater localities from Angmagssalik district, Southeast Greenland, were placed at my disposal. In the collection 12 species of Entomostraca were found, three of them, Alonella nana, Leptodiaptomus minutus and Bryocamptus ( Arcticocamptus) arcticus are new to East Greenland, and Candona rectangula is new to Southeast Greenland. A comparation is made between the entomostracal fauna of Southwest Greenland, Southeast Greenland, and the Scoresby Sund area, and some zoogeographical remarks are given.